F-actin changes and Hippo pathway regulation: An analysis of F-actin in different tumor models of liver cancer - Pinto Gualpa, Josué Nicolás (2019)
F-actin is important for multiple cellular processes such as cell adhesion, motility and division. Additionally, it has been demonstrated to play an important role in cancer progression and the regulation of different signaling pathways. Previous studies by our group and others have revealed that, in Drosophila, F-actin acts as an upstream regulator of YAP, the transcriptional effector of the Hippo pathway. However, it remains unknown if actin polymerization is important for YAP activation in mammalian tumors. In this study, we analyzed F-actin levels in cancer cells of four models of liver cancer driven by different oncogenes delivered by hydrodynamic tail vein injection in mice. To compare the levels and localization of F-actin in normal and cancer cells, we used an immunofluorescence assay. We found a striking increase in the levels of F-actin in cancer cells of tumors from intrahepatic cholangiocarcinoma (ICC), hepatocellular carcinoma (HCC) and a combined model of ICC and HCC. Furthermore, the correlation between actin levels and YAP phosphorylation status in tumor cells was analyzed. Immunoblot analysis showed that YAP phosphorylation is significantly decreased in cancer cells of ICC tumors, but only somewhat decreased in cancer cells of HCC tumors. Altogether, our analysis revealed an important correlation in the regulation between the levels of Factin and the activation status of the Hippo pathway and suggests an essential role of actin polymerization in tumor progression.